Kemampuan Berpikir Refraktif Matematis Mahasiswa melalui Pembelajaran Peer-Assited Reflection - Isra Nurmai Yenti; Yaya S. Kusumah; Jarnawi Afghani Dahlan (Jurnal Elemen, 2021)
Refractive thinking needs to be developed in lectures because it has an essential role in decision-making. However, so far, there has not been found any relevant research that develops refractive thinking through applying a learning strategy. The purpose of this study was to obtain an overview of the enhancement of students' mathematical refractive thinking ability based on prior mathematical knowledge through the application of Peer-Assisted Reflection learning and the influence of the interaction of learning factors and the level of prior mathematical knowledge on enhancing mathematical refractive thinking ability. This research is a quantitative study with a quasi-experimental design. Using the purposive sampling technique, 73 students were selected to take the Multivariable Calculus course. The research sample was students who took the Multivariable Calculus course. The instrument used was a prior mathematical knowledge test and a mathematical refractive thinking ability test. Data analysis used t-test, tâ€™-test, Mann-Whitney U test, Aligned Rank Transform, and two-way ANOVA. The findings of this study are: (1) The enhancement of students' mathematical refractive thinking ability who got Peer-Assisted Reflection learning is better than those who got conventional learning for all levels of prior mathematical knowledge; and (2) There is no significant effect on the interaction between learning and prior mathematical knowledge on improving mathematical refractive thinking ability.